Upgrading transmission line capability by AC–DC conversion. (May 2018) - Manickam, Raju; Palaniappan, Subramaniam Nettiampalayam
Abstract: In recent times, it has been very difficult to build corridors for new overhead lines in industrialized countries like India due to various constraints. To avoid such complicated implementation, building of new infrastructure, new methods are required to upgrade conventional overhead lines. The conversion from AC to DC lines is an alternative way to upgrade the capability of power transmission in order to avoid Rights Of Way (ROW) issues. Hence, in this paper, a methodology is adapted to convert the High Voltage AC (HVAC) line and High Voltage DC (HVDC) for improved power transmission. Electric Field Intensity and Magnetic Field Intensity are evaluated and a real-time data over 400 kV transmission network is analysed to test its performance. The identified network is also analysed under steady and dynamic state with ETAP/PSS/E tool to measure the performance of power transmitted. Further, load flow analysis, short circuit and transient stability are also studied to check the efficacy of the methods adopted to convert HVAC to HVDC lines.